Bi@Sn Core–Shell Structure with Compressive Strain Boosts the Electroreduction of CO2 into Formic Acid. Issue 22 (1st October 2020) - Xing, Yulin; Kong, Xiangdong; Guo, Xu; Liu, Yan; Li, Qiuyao; Zhang, Yuzhe; Sheng, Yelin; Yang, Xupeng; Geng, Zhigang; Zeng, Jie
Abstract: As a profitable product from CO2 electroreduction, HCOOH holds economic viability only when the selectivity is higher than 90% with current density ( j ) over −200.0 mA cm −2 . Herein, Bi@Sn core–shell nanoparticles (Bi core and Sn shell, denoted as Bi@Sn NPs) are developed to boost the activity and selectivity of CO2 electroreduction into HCOOH. In an H‐cell system with 0.5 m KHCO3 as electrolyte, Bi@Sn NPs exhibit a Faradaic efficiency for HCOOH (FEHCOOH ) of 91% with partial j for HCOOH ( j HCOOH ) of −31.0 mA cm −2 at −1.1 V versus reversible hydrogen electrode. The potential application of Bi@Sn NPs is testified via chronopotentiometric measurements in the flow‐cell system with 2.0 m KHCO3 electrolyte. Under this circumstance, Bi@Sn NPs achieve an FEHCOOH of 92% with an energy efficiency of 56% at steady‐state j of −250.0 mA cm −2 . Theoretical studies indicate that the energy barrier of the potential‐limiting step for the formation of HCOOH is decreased owing to the compressive strain in the Sn shell, resulting in the enhanced catalytic performance. Abstract : Bi@Sn core–shell nanoparticles (Bi core and Sn shell) are developed to boost the activity and selectivity of CO2 electroreduction into HCOOH. The lattice mismatch between the Bi core and Sn shell generates a compressive strain in the Sn shell. The compressive strain in the Sn shell decreases the energy barrier for the formation of HCOOH, resulting in the enhanced catalytic performance.